2000
DOI: 10.1016/s1161-0301(99)00050-7
|View full text |Cite
|
Sign up to set email alerts
|

Ultraviolet-B radiation and nitrogen effects on growth and yield of maize under Mediterranean field conditions

Abstract: The effects of an increase in UV-B radiation on growth and yield of maize (Zea mays L.) were investigated at four levels of applied nitrogen (0, 100, 200 and 300 kg ha− 1 of N) under Mediterranean field conditions. The experiment simulated a 20% stratospheric ozone depletion over Portugal. Enhanced UV-B and N deficiency decreased yield and total biomass production by 22-49%. High UV-B dose reduced yield, total biomass and growth of N-fertilized maize plants but did not affect N-stressed plants to the same exte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
1
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 42 publications
2
18
1
2
Order By: Relevance
“…Such results suggest that not only the future enhanced UV-B will present a threat to buckwheat growth and production, but also the present ambient solar UV-B significantly affects tartary buckwheat. The response of enhanced UV-B on the growth and production of tartary buckwheat was consistent with the studies on the responses of 20 soybean cultivars (Li et al, 2002) and 20 wheat cultivars (Li et al, 2000) in the same experimental location, and with the investigations on the field responses of maize (Correia et al, 2000), cotton (Gao et al, 2003) and barley (Hakala et al, 2002) in different locations. In those studies the effect of future ozone depletion was probably exaggerated because the enhanced/ambient UV-B ratio was always elevated under cloudy weather (Allen et al, 1999;Flint et al, 2003), but the trend of growth inhibition by enhanced UV-B was consistent.…”
Section: Effect Of Uv-b Radiation On Plant Growth Development and Prsupporting
confidence: 89%
“…Such results suggest that not only the future enhanced UV-B will present a threat to buckwheat growth and production, but also the present ambient solar UV-B significantly affects tartary buckwheat. The response of enhanced UV-B on the growth and production of tartary buckwheat was consistent with the studies on the responses of 20 soybean cultivars (Li et al, 2002) and 20 wheat cultivars (Li et al, 2000) in the same experimental location, and with the investigations on the field responses of maize (Correia et al, 2000), cotton (Gao et al, 2003) and barley (Hakala et al, 2002) in different locations. In those studies the effect of future ozone depletion was probably exaggerated because the enhanced/ambient UV-B ratio was always elevated under cloudy weather (Allen et al, 1999;Flint et al, 2003), but the trend of growth inhibition by enhanced UV-B was consistent.…”
Section: Effect Of Uv-b Radiation On Plant Growth Development and Prsupporting
confidence: 89%
“…That aspect is confirmed by nutrient concentrations changes from silking to maturity harvest mainly because of redistribution during grain filling, which in turn is a function of the demand and the sink strength of the grains and of the mobility of the elements within the plants. Earlier senescence and lower photosynthesis promoted by high UV-B were reported previously in maize [6, 11, 12, 28]. Furthermore, the changes in the amount of nutrients acquired by maize shoot under enhanced UV-B will have implications on nutrient cycling within the plant-soil system.…”
Section: Discussionmentioning
confidence: 61%
“…However, as there are no two elements with identical responses to UV-B radiation, optimisation of fertiliser practice in an enhanced UV-B environment would offer a considerable challenge. Several explanations can be given for the reduction of nutrient uptake under high UV-B, including the lower transpiration rate, as reported earlier [12], the inhibition of the activity of nitrate reductase and other key enzymes of nitrogen metabolism [26], the inhibition of ATP synthesis [27], and the decrease of photosynthesis and carbohydrate availability [11]. Despite lower nutrient uptake, these data do not indicate any kind of severe nutrient limitation in high UV-B treated plants.…”
Section: Discussionmentioning
confidence: 99%
“…However, carbohydrate accumulation in leaves during photosynthesis is a common phenomenon that can be enhanced by a low sink demand (Neales and Incoll, 1968). As UV-B radiation treated plants are known to have a tendency to have a lower sink capacity (Correia et al, 2000), the observed decreases in the C content of leaves induced by UV-B radiation indicate that the main response is mediated by a lower net photosynthetic rate. Similar results have been reported by Mackerness et al (1997).…”
Section: The Growth and Physiological Responses As Affected By Enhancmentioning
confidence: 99%